Virtual simulator for mobile robots navigation systems - De Melo, Leonimer Flávio; Rosário, João Maurício; Ferasoli Filho, Humberto [UNESP]; Prado, José Guilherme Simão [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
This paper presents the virtual environment implementation for project simulation and conception of supervision and control systems for mobile robots, that are capable to operate and adapting in different environments and conditions. This virtual system has as purpose to facilitate the development of embedded architecture systems, emphasizing the implementation of tools that allow the simulation of the kinematic conditions, dynamic and control, with real time monitoring of all important system points. For this, an open control architecture is proposal, integrating the two main techniques of robotic control implementation in the hardware level: systems microprocessors and reconfigurable hardware devices. The implemented simulator system is composed of a trajectory generating module, a kinematic and dynamic simulator module and of a analysis module of results and errors. All the kinematic and dynamic results shown during the simulation can be evaluated and visualized in graphs and tables formats, in the results analysis module, allowing an improvement in the system, minimizing the errors with the necessary adjustments optimization. For controller implementation in the embedded system, it uses the rapid prototyping, that is the technology that allows, in set with the virtual simulation environment, the development of a controller project for mobile robots. The validation and tests had been accomplish with nonholonomics mobile robots models with diferencial transmission. © 2008 IEEE.
Keywords: Concurrent engineering; Embedded systems; Error analysis; Errors; Integrated circuits; Job analysis; Kinematics; Mobile robots; Rapid prototyping; Real time systems; Robotics; Robots; Simulators; Virtual reality; Control applications; Control architectures; Controller implementation; Dynamic simulators; Embedded architectures; International conferences; Kinematic conditions; Nonholonomics; Project simulation; Prototyping; Real-time monitoring; Reconfigurable hardware devices; Robotic controls; Virtual environment; Virtual simulation environment; Virtual simulators; Virtual systems; Control systems